(3VeGfGJ GdMHS GdGMJjGWj (B: s (3OQGSI ebGQfI Hjf GdfXGe GdSYhOj hGdbGfhf GdeUQj (B/ s - (3CcQe MejO YHjO Gddg GdTYjHis; (3YeQ eMeO SGde s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2010)
(3cTa GdHMK VeGfGJ GdMHS GdGMJjGWj OQGSI ebGQfI Hjf GdfXGe GdSYhOj hGdbGfhf GdeUQj eGjbJVjg gPG GdHMK Yf eGgjJg GP JVef GdHMK ef eGgjI VeGfGJ GdMHS GdGMJjGWi hPdc ef NdGd GSJYQGV eaghe VeGfGJ GdMHS GdGMJjGWi heGGTJed Ydi JYQjag dZI (B: (3hGUWdGMB (B: (3heGJhUd Gdjg Gdabg GdLfGFi ef JYQja jMOO EWGQg GdbGfhfi hjMOO edGeMg aj fWGb eGQSeg GdfXGe (B: (3jVGa Gdi Pdc GdJaQbI Hjfg hHjf eGjTGHgg ef GdELQGAGJ GdJj JeS GdMQjI GdTNUjI Gh JbjOgG daJQI RefjIs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2010s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B259-270s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GdGaQGL GdeDbJs; (3GdMHS GdGMJjGWj s; (3GdVeGfGJ s; (3GdJhbja GdGMJjGWis; (3GdJMbjb GdGHJOGFis; (3GdGSJLhGHs; (3GdGaQGL GdeDbJs; (3eQGbHI GdTQWIs; (3GdGbGeI GdLHQjIs; (3GdefY ef GdSaQs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs